Targeting Transient Receptor Potential (TRP) Channels, Mas-Related G-Protein-Coupled Receptors (Mrgprs), and Protease-Activated Receptors (PARs) to Relieve Itch - Merab G. Tsagareli; Taylor Follansbee; Mirela Iodi Carstens; Earl Carstens (MDPI AG, 2023)
Itch (pruritus) is a sensation in the skin that provokes the desire to scratch. The sensation of itch is mediated through a subclass of primary afferent sensory neurons, termed pruriceptors, which express molecular receptors that are activated by itch-evoking ligands. Also expressed in pruriceptors are several types of Transient Receptor Potential (TRP) channels. TRP channels are a diverse class of cation channels that are responsive to various somatosensory stimuli like touch, pain, itch, and temperature. In pruriceptors, TRP channels can be activated through intracellular signaling cascades initiated by pruritogen receptors and underly neuronal activation. In this review, we discuss the role of TRP channels TRPA1, TRPV1, TRPV2, TRPV3, TRPV4, TRPM8, and TRPC3/4 in acute and chronic pruritus. Since these channels often mediate itch in association with pruritogen receptors, we also discuss Mas-related G-protein-coupled receptors (Mrgprs) and protease-activated receptors (PARs). Additionally, we cover the exciting therapeutic targets amongst the TRP family, as well as Mrgprs and PARs for the treatment of pruritus.